Surface sliding mode controller for chaotic oscillation in power system with power disturbance - Fuhong MIN; Hanyuan MA; Yaoda WANG (Tongxin xuebao)
With the rapid development of the power industry,the possibility of chaotic oscillation increases in the power system,and the importance of maintaining the stability of the power system is prominent.Through a fourth-order power system model with power perturbation term built,the Lyapunov exponent spectrum,bifurcation diagram and spectral entropy were analyzed,respectively.The influence of power disturbance terms on power system motion was discussed in detail.Moreover,a dynamic surface sliding mode controller was designed based on the switching function with relay characteristics.Simulation results show that the controller can suppress the chaotic oscillation quickly and smoothly,and effectively avoid chattering and own strong robustness.